Experimental characterization of multi-layer 3D-printed shields for microsatellites. Issue 2 (June 2020) - Olivieri, Lorenzo; Giacomuzzo, Cinzia; Francesconi, Alessandro; Stokes, Hedley; Rossi, Alessandro
Highlights: 3D printed aluminium shields for small satellites have been manufactured and tested. Different geometries are proposed (multi-shock, corrugated, hybrid). HVI tests suggest an enhanced capability of 3D printed shields to fragment impacting projectiles. Abstract: In recent years, innovative processes such as additive manufacturing are finding application in the satellite industry, allowing solutions of which implementation could have been difficult or expensive using traditional manufacturing techniques. In the framework of the EU H2020 ReDSHIFT project, new 3D printed shields were developed for microsatellites protection: (1) a multi-shock panel comprising four equally-spaced 3D printed bumper layers, (2) a two-walls panel with outer bumper layers sandwiching a corrugated core, and (3) a hybrid panel with three equally-spaced bumpers, and a fourth corrugated bumper sandwiched between two of them. These shields were evaluated with respect to their resistance to hypervelocity impacts of mm-size debris expectable in the LEO environment. This paper presents the results of HVI tests carried out at the University of Padova on the proposed panels: debris-shielding properties were evaluated with respect to the damage on targets and witness plates placed behind them. Debris clouds resulting from panels perforation were also observed qualitatively through high-speed imaging. Compared to standard honeycomb panels, all the proposed shields showed improvements in terms of debris shielding.